Thermal Performance Analysis and Empirical Correlations for Laminar Forced Convection over 30 V-Baffled Square Channel - Amnart Boonloi; Withada Jedsadaratanachai (My University, 2014)
Thermal performance analysis for laminar forced convection in an isothermal wall square channel with 30° V-baffle is presented numerically. The parameters of the V-baffle, blockage ratio (b/H, BR), pitch ratio (P/H, PR), flow direction (V-Downstream and V-Upstream), and arrangement (in-line and staggered), are studied and compared with the previous works, 20° and 45° V-baffle. The Reynolds number based on the hydraulic diameter of the channel ( D h ), Re = 100–2000, is used in range study. The results show that the flow configurations of 30° V-baffle are found similar as 20° and 45° V-baffle. The fully developed periodic flow and heat transfer are created around 7th-8th module, while the periodic flow and heat transfer profiles are found at 2nd module in all cases. Except for the periodic concept, the 30° V-baffle can help to reduce the pressure loss around 2.3 times in comparison with the 45° V-baffle at the maximum f/ f 0 value (BR = 0.3, PR = 1, V-Downstream). The optimum thermal enhancement factor for the 30° V-baffle is found around 4.25 at BR = 0.15, PR = 1, and Re = 2000 for V-Downstream case with in-line arrangement.
Keywords: Baffle; Forced convection; Heat transfer enhancement; Heat Transfer Mechanisms